Assessing the Effects of Wives' Earnings on Family Income Inequality - Cancian, Maria; Reed, Deborah (The Review of Economics and Statistics, 1998)
We argue that the effect of wives' earnings can be assessed meaningfully only by comparing the observed distribution of income with a reference distribution. The components of the standard decomposition of the Gini coefficient have no implicit reference distribution and therefore should not be interpreted as a measure of the effect of an income source on inequality. We suggest several intuitive counterfactual reference distributions and illustrate their use with 1979 and 1989 U.S. data. We conclude that wives' earnings reduced inequality in that the income distribution would have been less equal in their absence. Alternative measures of the impact have mixed results.